Carbon nanotube-aerogel-aluminum silicate super-hydrophobic anti-icing material and preparation method thereof
By attaching a superhydrophobic composite coating composed of carbon nanotubes and aerogel to the aluminum silicate fiber substrate, the existing superhydrophobic materials have been solved, and the anti-icing performance of anti-icing and de-icing performance in high-humidity environments is achieved, and the photothermal de-icing effect is achieved, and excellent environmental friendliness and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510196975.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-06-13
AI Technical Summary
The existing superhydrophobic materials have insufficient anti-icing and de-icing performance in high humidity environments, and the photothermal conversion performance of the photothermal superhydrophobic materials is low, which cannot meet the requirements of anti-icing on the surface of outdoor equipment.
The super-hydrophobic anti-ice material of carbon nanotube-aerogel-aluminum silicate is used to improve the hydrophobicity and photothermal conversion efficiency of the material and reduce heat loss by attaching a super-hydrophobic composite coating composed of carbon nanotubes and aerogel to the aluminum silicate fiber substrate.
It improves the moisture-proof and heat insulation ability of the material in a high humidity environment, enhances the photothermal deicing efficiency, extends the freezing time of the droplets on the surface, and has excellent performance in green and environmentally friendly and corrosion-resistant.
Smart Images

Figure CN120138989A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of superhydrophobic functional materials, and particularly to a carbon nanotube - aerogel - aluminum silicate superhydrophobic anti - icing material and a preparation method thereof. Background Art
[0002] Icing is a common natural phenomenon. However, in many fields such as electricity, aviation, energy, and transportation, icing on the surface of outdoor engineering equipment will cause significant hazards and safety risks. Existing methods for removing surface ice can be divided into active de - icing methods and passive anti - icing methods. Active de - icing methods include mechanical de - icing, thermal de - icing, chemical de - icing, etc. Active de - icing methods are mostly based on the idea of de - icing and melting ice after icing, and have many disadvantages such as high energy consumption, high cost, high pollution, and low efficiency, and cannot solve the anti - icing and de - icing problems in the field of engineering equipment. Passive anti - icing methods use the surface structure or inherent properties of materials to delay, reduce or even prevent icing, and have the advantages of low energy consumption, environmental friendliness, and wide application range. Among them, superhydrophobic surfaces with multi - level micro - nano structures and low surface energy are considered ideal passive anti - icing surfaces because of their unique surface hydrophobicity, which can delay the icing time and reduce the adhesion strength between the ice - solid interface. However, the existing superhydrophobic surface structures are easy to form interlocks with ice layers, and in high - humidity environments, small droplets are easy to penetrate into the micro - structures, resulting in the failure of the surface anti - icing and de - icing properties.
[0003] Photothermal superhydrophobic materials combine photothermal materials with superhydrophobic materials, convert light energy into heat energy, and use micro - nano structures to improve the photothermal conversion efficiency and photothermal conversion temperature, so that the ice on the ice - solid interface can fall off automatically by virtue of the low adhesion of the superhydrophobic surface after melting, with the characteristics of green and high efficiency. However, the existing photothermal superhydrophobic materials have low photothermal conversion performance on the surface and large heat loss, and still cannot meet the requirements of anti - icing and de - icing on the surface of outdoor equipment at the present stage.
[0004] Aluminum silicate fiber is a new type of thermal insulation material, which has the advantages of light weight, high temperature resistance, good flexibility, non - toxicity, high tensile and flexural strength, and is widely used in pipeline, boiler and exterior wall thermal insulation materials. Using aluminum silicate fiber as a thermal insulation layer can effectively reduce the heat loss of the photothermal superhydrophobic surface. However, aluminum silicate fiber is hydrophilic, and its thermal insulation performance decreases in outdoor high - humidity environments, and it cannot meet the requirements of surface thermal insulation, moisture protection and anti - icing in high - humidity environments. Summary of the Invention
[0005] Aiming at the above - mentioned existing technical deficiencies, the purpose of the present invention is to provide a carbon nanotube - aerogel - aluminum silicate superhydrophobic anti - icing material and a preparation method thereof, which can not only improve the moisture - proof and heat - insulation capabilities of aluminum silicate fiber when used in outdoor high - humidity environments, but also reduce the photothermal conversion loss due to its superhydrophobic surface, thereby improving the photothermal de - icing efficiency of the surface.
[0006] To solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The present invention provides a carbon nanotube - aerogel - aluminum silicate superhydrophobic anti - icing material, comprising:
[0008] (a) An aluminum silicate fiber substrate with a thickness of 1 - 10 mm and a fiber diameter of 50 - 100 μm;
[0009] (b) A photothermal carbon nanotube - aerogel superhydrophobic composite coating attached to the surface of the aluminum silicate fiber substrate; the composite coating is formed by curing a composite solution containing the following components:
[0010] Carbon nanotubes: accounting for 5 wt% - 30 wt% of the total mass of the resin;
[0011] Silica aerogel particles: accounting for 8 wt% of the total mass of the resin, with a porosity > 90%, a bulk density of 0.05 - 0.15 g / cm 3 , and a particle size of 5 - 50 nm;
[0012] Resin: selected from one or a 2:1 mixture of two of epoxy resin - based resins and silicone rubber - based resins;
[0013] Low - surface - energy modifier: selected from any one of octadecyltrimethoxysilane, hexadecyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, or tridecafluorooctyltrimethoxysilane; accounting for 0.5 wt% - 1 wt% of the total mass of the composite solution;
[0014] Diluent: a solution obtained by mixing anhydrous ethanol and ethyl acetate in a volume ratio of 4:1.
[0015] Preferably, the aluminum silicate fiber substrate is cleaned with anhydrous ethanol and dried before coating.
[0016] Preferably, the epoxy resin - based resins include E - 44 epoxy resin and E - 51 epoxy resin, and the silicone rubber - based resin is polydimethylsiloxane resin, including PDMS resin and Dow Corning DC - 184 resin.
[0017] The present invention also provides a preparation method of the above - mentioned carbon nanotube - aerogel - aluminum silicate superhydrophobic anti - icing material, comprising the following steps:
[0018] S1. Add carbon nanotubes and silica aerogel particles to the diluent in proportion, stir and mix, and form a uniform mixed solution after ultrasonic dispersion. Add a low - surface - energy modifier thereto and stir at room temperature for 6 - 8 hours to obtain a photothermal superhydrophobic particle solution;
[0019] S2. Add the resin to the solution obtained in step S1, stir at room temperature for 1 - 2 hours and then perform ultrasonic dispersion for 5 - 20 minutes to obtain a photothermal superhydrophobic coating solution;
[0020] S3. After cleaning and drying the aluminosilicate fiber substrate, attach the coating solution obtained in step S2 to its surface by spraying, immersion or brushing, and then cure it in a constant temperature drying oven at 60 - 80 °C for 1 - 3 hours to form the composite material.
[0021] Preferably, the mixing ratio of the mass ratio of carbon nanotubes to silica aerogel particles in step S1 is 1:2 - 2.5:1.
[0022] Preferably, the surface coating thickness of the aluminosilicate fiber substrate after coating in step S3 is 100 μm.
[0023] Preferably, the surface of the aluminosilicate fiber substrate after coating in step S3 has superhydrophobicity (e.g., contact angle > 150°).
[0024] The beneficial effects of the present invention are as follows:
[0025] (1) In the present invention, carbon nanotubes and aerogel particles are mixed, so that the carbon nanotubes and aerogel particles produce micro - agglomeration, generating micro - nano composite particles with multi - level roughness, and using the good photothermal effect of carbon nanotubes and the good hydrophobicity and low thermal conductivity of aerogel particles, the surface hydrophobicity and photothermal conversion efficiency can be improved simultaneously, and the surface heat loss can be reduced.
[0026] (2) Utilizing the high porosity of aluminosilicate fiber, the light absorption efficiency can be improved, thereby improving the surface photothermal conversion efficiency. At the same time, the low thermal conductivity of aluminosilicate fiber can prevent the heat generated by surface photothermal conversion from being lost longitudinally along the material, and can further improve the surface photothermal conversion temperature rise.
[0027] (3) In the present invention, aluminosilicate fiber belongs to a flexible substrate. Utilizing its high flexibility, the ice adhesion force between ice and the fiber surface can be reduced, and the anti - icing ability of the surface can be improved.
[0028] (4) After illumination, a large amount of heat will be generated on the surface of the photothermal superhydrophobic aluminosilicate fiber prepared by the present invention, melting the accumulated ice at the interface, and then removing the accumulated ice by virtue of the lower water rolling angle of the superhydrophobic surface.. Description of the Drawings
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0030] Figure 1 It is the SEM image of the surface morphology of the photothermal carbon nanotube - aerogel - aluminosilicate fiber superhydrophobic material;
[0031] Figure 2 Contact angle diagram of the photothermal carbon nanotube - aerogel - aluminosilicate fiber superhydrophobic material;
[0032] Figure 3 Self - cleaning diagram of the photothermal carbon nanotube - aerogel - aluminosilicate fiber superhydrophobic material;
[0033] Figure 4 Photothermal temperature cycling curve of the photothermal carbon nanotube - aerogel - aluminosilicate fiber superhydrophobic material under sunlight intensity of 1 kW / m2;
[0034] Figure 5 Photothermal anti - icing performance diagram of the photothermal carbon nanotube - aerogel - aluminosilicate fiber superhydrophobic material. Specific implementation manners
[0035] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0036] Embodiment 1. The embodiment of the present invention provides a carbon nanotube - aerogel - aluminosilicate superhydrophobic anti - icing material, including:
[0037] (a) An aluminosilicate fiber substrate with a thickness of 1 - 10 mm and a fiber diameter of 50 - 100 μm;
[0038] (b) A photothermal carbon nanotube - aerogel superhydrophobic composite coating attached to the surface of the aluminosilicate fiber substrate; the composite coating is formed by curing a composite solution containing the following components:
[0039] Carbon nanotubes: accounting for 12 wt.% of the total mass of the resin;
[0040] Silica aerogel particles: porosity > 90%, bulk density of 0.05 - 0.15 g / cm 3 , particle size of 5 - 50 nm, accounting for 8 Wt% of the total mass of the resin;
[0041] Resin: a 2:1 mixture of E - 51 resin selected from epoxy resin - type resins and PDMS resin selected from silicone rubber - type resins;
[0042] Low - surface - energy modifier: selected from 1H,1H,2H,2H - perfluorodecyltrimethoxysilane;
[0043] Diluent: a solution of anhydrous ethanol and ethyl acetate mixed at a volume ratio of 4:1.
[0044] The preparation method of the carbon nanotube-aerogel-aluminosilicate superhydrophobic anti-icing material includes the following steps:
[0045] Step S1: Add 0.3 g of carbon nanotubes and 0.2 g of aerogel particles to 20 mL of a mixed solution of absolute ethanol and ethyl acetate, where the volume ratio of the absolute ethanol and ethyl acetate mixed solution is 4:1, stir and mix, ultrasonically disperse for 20 min to form a uniform mixed solution. Add 200 μL of heptadecafluorodecyltrimethoxysilane to the mixed solution. After adding, stir at room temperature for 6 h to obtain a photothermal superhydrophobic particle solution.
[0046] Step S2: Add 1.5 g of epoxy resin and 0.75 g of PDMS resin to the photothermal superhydrophobic particle solution, stir at room temperature for 1 h, and ultrasonically disperse for 20 min to form a slurry.
[0047] Step S3: Add 0.5 g of epoxy resin curing agent and 0.075 g of PDMS resin curing agent to the slurry prepared in Step S2, stir at room temperature for 20 min to form a photothermal superhydrophobic coating.
[0048] Step S4: Wash the 1-mm-thick aluminosilicate fiber material with absolute ethanol to remove surface oil stains. After drying, use this as a substrate, attach the photothermal superhydrophobic coating solution obtained in Step S3 to the surface of the aluminosilicate fiber material by spraying method, and then place it in an 80°C constant temperature drying oven for 3 h to cure the resin, thereby obtaining the carbon nanotube-aerogel-aluminosilicate superhydrophobic anti-icing material.
[0049] The surface SEM image of the carbon nanotube-aerogel-aluminosilicate superhydrophobic anti-icing material is shown in Figure 1 . Compared with the original aluminosilicate fiber, the surface of the prepared carbon nanotube-aerogel-aluminosilicate superhydrophobic anti-icing material has a large number of micro-nano composite structures, greatly reducing the true solid-liquid contact area; the contact angle image of this material is shown in Figure 2 . The water droplets show a spherical shape on the surface, indicating that the surface has good hydrophobicity; the self-cleaning performance image of this material is shown in Figure 3 . The surface dust can be washed away by water droplets, achieving the effect of surface self-cleaning; the photothermal temperature cycle curve of this surface under 1 kW / m 2 solar light intensity irradiation is shown in Figure 4 . The temperature of the surface can be stabilized at 103°C under multiple 1 kW / m 2 solar light intensity irradiations; the photothermal anti-icing performance of this material is shown in Figure 5 . The surface of the prepared carbon nanotube-aerogel-aluminosilicate superhydrophobic anti-icing material can extend the icing time of water droplets on the surface at -5°C to -20°C.
[0050] Example 2
[0051] This example is based on Example 1, and the difference from Example 1 is that the addition amount of carbon nanotubes is 0.1 g, and the mass percentage in the resin is 4 wt.%.
[0052] Example 3
[0053] This example is based on Example 1, and the difference from Example 1 is that the addition amount of carbon nanotubes is 0.2 g, and the mass percentage in the resin is 8 wt.%.
[0054] Example 4
[0055] This example is based on Example 1, and the difference from Example 1 is that the addition amount of carbon nanotubes is 0.4 g, and the mass percentage in the resin is 17 wt.%.
[0056] Example 5
[0057] This example is based on Example 1, and the difference from Example 1 is that the addition amount of carbon nanotubes is 0.5 g, and the mass percentage in the resin is 22 wt.%.
[0058] Comparative Example 1:
[0059] This example is based on Example 1, and the difference from Example 1 is that the addition amount of carbon nanotubes is 0 g, and the mass percentage in the resin is 0 wt.%.
[0060] The coatings prepared in Examples 1 - 5 and Comparative Example 1 were tested for contact angle and rolling angle, and the test results are shown in Table 1.
[0061] Table 1 Contact Angle and Rolling Angle of Materials
[0062] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Contact angle (°) 157.2 150.7 154.6 154.8 153.1 148.5 Rolling angle (°) 2.5 4 2.9 2.7 3.3 8.5
[0063] The results show that the hierarchical composite structure formed by MWCNT and nano - silica aerogel can effectively improve the wettability of the material surface, changing the surface from the unprocessed super - hydrophilic state to the low - adhesion super - hydrophobic state (contact angle > 150°, rolling angle less than 5°). When MWCNT is not added, the surface cannot reach the super - hydrophobic state. This is because: the particle size of nano - silica aerogel is relatively small, at the nanometer level, and the number of particles is small and cannot form a micron - level structure. Therefore, although the contact angle is close to 150°, the rolling angle is large.
[0064] The aluminosilicate fiber super - hydrophobic materials prepared in Examples 1 - 5 and Comparative Example 1 were placed under sunlight irradiation with an intensity of 1 kW / m2 for 30 min, and a temperature detector was used to record the change in the surface temperature of the aluminosilicate fiber super - hydrophobic material with the irradiation time. The test results are shown in Table 2.
[0065] Table 2 Surface Temperature of Materials
[0066] 0 min 10 min 30 min Example 1 21.5 102.6 103.1 Example 2 22.1 92.8 93.6 Example 3 22.1 98.3 98.5 Example 4 20.1 98.2 99.1 Example 5 20.1 99.4 99.8 Comparative Example 1 21.2 25.8 26.8
[0067] As can be seen from Table 2, the addition of an appropriate amount of MWCNT can significantly increase the surface temperature of the coating. This is because MWCNT produces a good photothermal effect under light irradiation. However, the addition of MWCNT cannot be excessive. Excessive addition of MWCNT will instead reduce the surface temperature. This is because excessive MWCNT is prone to agglomeration, which will instead reduce the photothermal conversion efficiency. Therefore, the prepared photothermal carbon nanotube-aerogel-aluminum silicate fiber superhydrophobic material has the ability to provide thermal energy to inhibit icing. Considering the photothermal conversion characteristics and superhydrophobicity comprehensively, 0.3 g of carbon nanotubes with a mass percentage of 12 wt.% in the resin is used as the optimal addition amount.
[0068] In summary, the present invention effectively solves the problems of poor moisture-proof and heat-insulation capabilities of aluminum silicate fiber when used in outdoor high-humidity environments, endows it with superhydrophobicity, reduces photothermal conversion losses, and thus improves the photothermal de-icing efficiency of the surface. By combining the high flexibility of aluminum silicate fiber with the photothermal superhydrophobic material, on the one hand, its flexibility is used to reduce the ice adhesion force between ice and the fiber surface, improving the anti-icing ability of the surface. On the other hand, the photothermal effect is used to melt the accumulated ice at the interface and remove the accumulated ice by virtue of the low adhesion of the superhydrophobic surface. The photothermal carbon nanotube-aerogel-aluminum silicate fiber superhydrophobic material described in the present invention has excellent properties such as green environmental protection, good corrosion resistance, superhydrophobicity, and long ice formation delay time.
[0069] Obviously, those skilled in the art can make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention also intends to include these modifications and variations.
Claims
1. Carbon nanotube-aerogel-aluminum silicate super hydrophobic anti-icing material, characterized in that: include: (a) an aluminum silicate fiber substrate having a thickness of 1-10 mm and a fiber diameter of 50-100 μm; (b) a photothermal carbon nanotube-aerogel super-hydrophobic composite coating attached to the surface of the aluminum silicate fiber substrate; the composite coating is formed by curing a composite solution comprising the following components: Carbon nanotubes: 5wt%-30wt% of the total mass of the resin; Silica aerogel particles: 8wt% of the total resin mass, porosity>90%, bulk density 0.05-0.15g / cm 3 , particle size is 5-50nm; Resin: selected from epoxy resin, silicone rubber resin or a 2:1 mixture of the two; Low surface energy modifier: any one selected from octadecyltrimethoxysilane, hexadecyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane or tridecafluorooctyltrimethoxysilane; accounting for 0.5wt%-1wt% of the total mass of the composite solution; Diluent: A solution of anhydrous ethanol and ethyl acetate mixed in a volume ratio of 4:
1.
2. The carbon nanotube-aerogel-aluminum silicate super hydrophobic anti-icing material according to claim 1, characterized in that: The aluminum silicate fiber substrate is cleaned and dried with anhydrous ethanol before coating.
3. The carbon nanotube-aerogel-aluminum silicate super hydrophobic anti-icing material according to claim 1, characterized in that: Epoxy resins include E-44 epoxy resin and E-51 epoxy resin, and silicone rubber resins are polydimethylsiloxane resins, including PDMS resin and Dow Corning DC-184 resin.
4. The method for preparing the carbon nanotube-aerogel-aluminum silicate super-hydrophobic anti-icing material according to claim 1, characterized in that: The following steps are involved: S1. The carbon nanotubes and silica aerogel particles are added to the diluent in proportion and stirred and mixed, and a uniform mixed solution is formed after ultrasonic dispersion, to which a low surface energy modifier is added, and stirred at room temperature for 6-8 hours to obtain a photothermal superhydrophobic particle solution; S2. The resin was added to the solution obtained in step S1, stirred at room temperature for 1-2 hours and ultrasonically dispersed for 5-20 minutes to obtain a photothermal super hydrophobic coating solution; S3. After cleaning and drying the aluminum silicate fiber substrate, the coating solution obtained in step S2 is attached to its surface by spraying, soaking or brushing, and then cured in a constant temperature drying oven at 60-80° C. for 1-3 hours to form the composite material.
5. The method according to claim 3, characterized in that In step S1, the mass ratio of the carbon nanotubes to the silica aerogel particles is 1:2-2.5:
1.
6. The method according to claim 3, characterized in that The coating thickness of the aluminum silicate fiber substrate surface after coating in step S3 is 100 μm.
7. The method according to claim 3, wherein the surface of the aluminum silicate fiber substrate after coating in step S3 has super hydrophobicity, and its contact angle is >150°.
Citation Information
Cited By
Cement-based aerogel heat preservation and heat insulation coating material for concrete and spraying construction technology of cement-based aerogel heat preservation and heat insulation coating material
CN120682655A
A cement-based aerogel thermal insulation coating material for concrete and its spraying application process
CN120682655B
A volume-stress temperature-sensitive self-regulating intelligent crack-resistant concrete material and its preparation method
CN122562452A
Volume-stress temperature-sensitive self-regulating intelligent anti-cracking concrete material and preparation method thereof
CN122562452B